Un objet d’histoire (presque) introuvable : les fourches patibulaires dans les sources tourangelles (xiiie-xviiie siècles) - Fabrice Mauclair (Criminocorpus)
From the example of Indre-et-Loire, this article examines the traces left by the gallows in the archival repositories of the French departments. If in the studied territory the ancient places of performance and exhibition have greatly changed the landscape (by inspiring many names) it is clear that they hardly appear in the sources. Indeed, during six centuries, less than fifteen major documents concerning them have been found. Thus, in Touraine, the few testimonies on the old gallows are in ecclesiastic texts and cartularies. In a secondary way, information about execution places and exhibition can be found among the archives from the judicial practice and illustrated documents. All these scattered traces can answer at several major issues. The first concerns the date of gallows appearance. The second deals with their duration, their frequency and their manner of use. Finally, the third relates their location, appearance and materials used in their construction.